Automatic Cybersecurity Analyzer for the Electric Sector - Oliveira, Lucas H. V.; Gurjão, Edmar Candeia (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on Cybersecurity, 2025)
This article simulates the automation of vulnerability analysis and risk assessment in power sector networks, using data from IEDs to extract the communication structure of substations. Based on SCL files, in compliance with IEC 61850, critical assets are mapped and compliance with security standards and OT policies is verified.